Lactic acid production by newly isolated bacteria from the larval gut of rhynchophorus ferrugineus / Siti Norazura bt Jamal - Jamal, Siti Norazura (2013)
In this study, the lactic acid bacteria profiles in the larvae gut were identified by using 16S rDNA and PCR-DGGE methods. The sequences obtained from sequencing were BLAST in BLASTN from DDBJ to identify the bacteria present in the larvae gut. From the BLASTN result, the sequences that have high score bit were Alcaligenes faecalis, Enterobacter aerogenes, Bordetella, and Bacillus subtilis. The lactic acid bacteria;Lactobacillus plantarum and Lactobacillus sakei also present in BLASTN result even the score bit was low. The sequences were aligned with Lactic acid bacteria sequence from GenBank to determine their relationship using CLUSTALW. A total of 25 bacterial isolates were isolated from three type of larvae gut of Rhynchophorus ferruginase gut i.e.fore gut, mid gut and hind gut. All the isolates were screened for catalase activity and gram staining. Out of these, eight isolate were subsequently identified as lactic acid bacteria i.e. they were catalase negative and gram positive. These isolates were put through gel plug test to distinguish between homofermentative and heterofermentative. Out of these, seven isolates were homofermentative which were successfully identified as lactic acid producer. Identification for carbohydrates utilization, sugar acid utilization and chemical sensitivity were done using Biolog® for premilinary physiological characterization. These seven isolates were subsequently put through a time course study using shake flask to monitor the biomass yield, end point pH and lactic acid production over 48 h period. Out of seven isolates, isolate (A9) was produced highest lactic acid production (g/L). Isolate (A9) was chosen for the study of interaction effect of temperature (°C), pH and NaCl (%) using full factorial statistical design.